Activatable photothermal agents with target-initiated large spectral separation for highly effective reduction of side effects. Issue 33 (15th July 2022) - Sun, Jie; Cheng, Ning; Yin, Kai; Wang, Rongchen; Zhu, Tianli; Gao, Jinzhu; Dong, Xuemei; Dong, Chengjun; Gu, Xianfeng; Zhao, Chunchang
Abstract : Activatable photothermal reagents were designed for cancer therapy. Dual-site-activatable probe showed a large spectral redshift of 150 nm in the presence of H2 O2, achieving truly selective activation to minimize side effects during PTT of cancers. Abstract : Photothermal agents (PTAs) with minimized side effects are critical for transforming cancer photothermal therapy (PTT) into clinical applications. However, most currently available PTAs lack true selective activation to reduce side effects because of heavy spectral overlap between photothermal agents and their corresponding products. This study reports the construction of activatable PTAs with target-initiated large spectral separation for highly effective reduction of side effects. Such designed probes involve two H2 O2 -activatable PTAs, aza-BOD-B1 (single activatable site) and aza-BOD-B2 (multiple activatable site). After interacting with H2 O2, aza-BOD-B1 only displays a mild absorption redshift (60 nm) from 750 nm to 810 nm with serious spectral overlap, resulting in a mild photothermal effect on normal tissues upon 808 nm light irradiation. In contrast, aza-BOD-B2 displays a large absorption spectral separation (150 nm) from 660 nm to 810 nm, achieving true selective activation to minimize side effects during PTT of cancer. Besides, in vitro and in vivo investigations demonstrated that aza-BOD-B2 can specifically induce photothermal ablation of cancer cells and tumors while leaving normal sites undamaged, whereas aza-BOD-B1 exhibits undesirable side effects on normal cells. Our study provides a practical solution to the problem of undesired side effects of phototherapy, an advance in precision medicine.